El relato como aparición: poéticas del agua y de lo velado. Conversación con Paula López Wood, autora de Animales extintos (2019). - Sandoval, Marcelo; Navarrete G., Carolina A. (Confluencia: Revista Hispánica de Cultura y Literatura)
The article focuses on the work and career of Paula López Wood, a Chilean communicator and writer, author of the short story anthology *Extinct Animals* (2019). Her work explores the relationship between human beings and the extreme territories of southern Chile, especially Patagonia and the Andes Mountain Range, combining genres such as travel writing and fiction to address themes like nature, trauma, and female voices. López Wood highlights the use of natural elements, especially water and ice, as narrative resources to express complex emotions and social wounds from a situated and sensitive perspective. She currently directs communications at the Chilean Museum of Pre-Columbian Art and is working on new projects that continue to explore travel literature and survival in the far south of America.